2014
DOI: 10.3168/jds.2013-6939
|View full text |Cite
|
Sign up to set email alerts
|

Serum iron as an indicator of acute inflammation in cattle

Abstract: The aim of this study was to assess the value of serum iron concentration in the diagnosis of acute inflammation in cattle. The diagnostic value of this approach was compared with that of various other hematological tests, including commonly used techniques that measure the levels of various other acute-phase proteins. The study population comprised 10 cows with acute traumatic reticuloperitonitis (RPT group) and 10 cows with acute mastitis (mastitis group) admitted to the Veterinary Teaching Hospital at Firat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 29 publications
(53 reference statements)
1
22
0
2
Order By: Relevance
“…It was reported that Fe deficiencies were triggered by cytokines in the time of the inflammatory response. It is stated that Fe concentrations decrease during the acute phase response (APR) in the organism due to inflammation in horses (Borges et al, 2007), dogs (Torrente et al, 2015), adult cattle (Baydar and Dabak 2014) and calves (Aydogdu et al, 2018). Baydar and Dabak (2014) stated that serum Fe concentration in cattle with mastitis and TRP is significantly decreased compared to the control group and serum Fe concentration may be a useful parameter for the determination of inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that Fe deficiencies were triggered by cytokines in the time of the inflammatory response. It is stated that Fe concentrations decrease during the acute phase response (APR) in the organism due to inflammation in horses (Borges et al, 2007), dogs (Torrente et al, 2015), adult cattle (Baydar and Dabak 2014) and calves (Aydogdu et al, 2018). Baydar and Dabak (2014) stated that serum Fe concentration in cattle with mastitis and TRP is significantly decreased compared to the control group and serum Fe concentration may be a useful parameter for the determination of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…It is stated that Fe concentrations decrease during the acute phase response (APR) in the organism due to inflammation in horses (Borges et al, 2007), dogs (Torrente et al, 2015), adult cattle (Baydar and Dabak 2014) and calves (Aydogdu et al, 2018). Baydar and Dabak (2014) stated that serum Fe concentration in cattle with mastitis and TRP is significantly decreased compared to the control group and serum Fe concentration may be a useful parameter for the determination of inflammation. Borges et al (2007) reported that the decrease in serum Fe concentration in horses is a sensitive marker of acute, subacute and chronic systemic inflammation, and the change in Fe concentration may be a useful parameter for monitoring response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that in humans with sepsis and SIRS, Fe concentrations are decreased and the monitoring of Fe concentrations may be beneficial (Shanbhogue and Paterson, 1990;Ayoglu et al, 2016). It is reported that in horses (Borges et al, 2007), dogs (Torrente et al, 2015), adult cattle (Baydar and Dabak, 2014) and calves (Aydogdu et al, 2018), Fe concentrations are decreased during acute phase response due to inflammatory reaction. It has been reported that in cattle with traumatic reticuloperitonitis (TRP) and mastitis, serum Fe concentrations are decreased compared to the control group and serum Fe concentrations in those diseases may be a useful parameter in the determination of inflammation (Baydar and Dabak, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that in horses (Borges et al, 2007), dogs (Torrente et al, 2015), adult cattle (Baydar and Dabak, 2014) and calves (Aydogdu et al, 2018), Fe concentrations are decreased during acute phase response due to inflammatory reaction. It has been reported that in cattle with traumatic reticuloperitonitis (TRP) and mastitis, serum Fe concentrations are decreased compared to the control group and serum Fe concentrations in those diseases may be a useful parameter in the determination of inflammation (Baydar and Dabak, 2014). In addition, it has been reported that decrease in the serum Fe concentrations in horses is a sensible marker for acute, subacute, and chronic systemic inflammation, and alteration in serum Fe concentration may be a useful parameter in monitoring the response to treatment (Borges et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Die ebenso analysierte Hepcidinkonzentration war vor der Behandlung mit durchschnittlich 58,4 ng/ml höher als nach der Behandlung (46,8 ng/ml) [42]. Ein Vergleich von Kühen mit Reticuloperitonitis oder Mastitis gegenüber gesunden Kontrolltieren ergab mittlere Serum-Fe-Konzentrationen von 6,0 µmol/l (Reticuloperitonitis), 7,8 µmol/l (Mastitis) und 26,8 µmol/l (Kontrollgruppe), woraus die Autoren eine Bedeutung von Fe als Entzündungsmarker für Einzeltiere und Herden ableiten [43]. Kürzlich wurde auch bei Entzündungen im Rahmen einer Enthornung ein signifikanter Abfall der mittleren Serum-Fe-Konzentration von 25,7 auf 16,1 µmol/l beschrieben [44].…”
Section: Hepcidin Und Entzündungsreaktionenunclassified